Extraction and Characterization of Natural Cellulosic Fiber From Jipijapa (Carludovica palmata) - Víctor M. Moo-Huchin (Science Faculty of Chiang Mai University, 2019)
Nowadays, natural fibers with their environmentally friendly qualities represent an important alternative to substitute the use of synthetic fibers in polymer matrix reinforcement. This study aimed to characterize cellulosic palmate fibers (CFE) extracted from the bundles of Jipijapa straw (BJS). The extraction of CFE was carried out by means of an acid hydrolysis, chlorination, alkaline extraction, and bleaching of the BJS. The physicochemical, thermal and mechanical properties of CFE were determined using techniques of FTIR, TGA, X-ray diffraction, AFM and SEM. The holocellulose content (55.70±3.00 %), lignin (23.71±1.01 %), ash (8.30±0.10 %), moisture (8.50±0.50 %) and extractives (10.10±0.50 %) of BJS, were comparable to those reported in the literature for other natural fibers. The spectroscopy FTIR, TGA and X-ray diffraction confirmed that CFE are rich in cellulose content and possess thermal stability, with a crystallinity index of 57 %. Based on the results of SEM, AFM, aspect ratio, mechanical properties, contact angle and surface energy, it was possible to determine and explain the potential application of CFE as reinforcement in the elaboration of biocomposite materials.